Компетентностный подход к образованию - Токтарова, Р.Е. (My University, 2013)
Оn the article of Toktarova R.E. on the theme “Competent approach to the education”. The article is aimed at the analysis of scientific literature studying the problem of a teacher’s competence. The attention is given to the definition “professional competence of a teacher”. Seven key educational competences are observed: competence on the value basis, cultural competence, cognitive competence, informative competence, communicative competence , socio-labour competence , competence of personal self-perfection and levels of educational model.